Effect of coronary tortuosity on invasive physiology. Issue 6 (10th June 2022) - Maznyczka, Annette; Rajkumar, Christopher; Hobson, Alex; Haworth, Peter AJ
Abstract : We present a case of angina, where extreme coronary tortuosity affected invasive physiology interpretation. Extreme coronary tortuosity may lower fractional flow reserve and instantaneous wave-free ratio. Therefore, invasive physiology can be misleading in this setting, when used to evaluate stenosis significance, or when used post-percutaneous coronary (PCI) intervention for physiology guided stent optimisation.